The Influence of Self‐Efficacy, Fear‐Avoidance Belief, and Coping Styles on Quality of Life for Chinese Patients with Chronic Nonspecific Low Back Pain: A Multisite Cross‐Sectional Study. Issue 6 (5th February 2018) - Du, Shizheng; Hu, Lingli; Bai, Yamei; Dong, Jianshu; Jin, Shengji; Zhang, Heng; Zhu, Ying
Abstract: Background: As a bio‐psycho‐social issue, chronic low back pain (CLBP) has been a significant topic in health management, and patients' quality of life (QOL) is gaining extensive attention. Self‐efficacy, pain fear‐avoidance belief (FAB), and coping styles play important roles in the QOL of CLBP patients. However, it remains unclear how self‐efficacy and FAB influence QOL through specific coping styles. This study aimed to explore the influencing paths of self‐efficacy, FAB, and coping styles on the QOL of patients with CLBP. Methods: This study relies on a multisite, cross‐sectional design involving 221 CLBP patients. Stepwise multiple regression and structural equation modeling were employed. Results: CLBP patients lived with a poor global QOL. Self‐efficacy played a direct, positive role in predicting QOL for patients with CLBP (β = 0.35), and it also played an indirect, positive role in predicting QOL (β = 0.19) through active coping styles (β = 0.31). FAB played a direct, negative role in predicting QOL (β = −0.33), and it also played an indirect, negative role in predicting QOL (β = −0.32) through passive coping styles (β = 0.32). Conclusions: Self‐efficacy and FAB are both directly and indirectly related to global QOL, and coping styles are important mediating variables. Self‐efficacy and active coping are protective factors for the QOL of CLBP patients, while FAB and passive coping are risk factors. Health education strategies are recommended by medical personnel to enhance CLBP patients' pain self‐efficacy, decrease pain FAB, and modify pain coping styles, so that their global QOL can be improved.